1989
DOI: 10.1007/bf02653667
|View full text |Cite
|
Sign up to set email alerts
|

Soymilk and tofu properties as influenced by soybean storage conditions

Abstract: Soybeans were stored at two temperatures, 20~ and 30~ and two relative humidities, 65% and 85%. The amount of protein extracted into soymilk decreased by about 14% of the initial extractability in all cases after eight months of storage. The decline in protein extractability could not be explained by decreases in pH, nor by loss of solubility of certain protein components. Tofu made from beans that were stored at 85% relative humidity became less uniform in microstructure toward the end of the storage period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
57
3
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 7 publications
12
57
3
3
Order By: Relevance
“…These results are in agreement with those observed by Thomas et al (1989), Chang (2004, 2008) and Kong et al (2008). During storage, the high temperature and relative humidity cause damage to grain tegument and activate the enzymes involved in aerobic respiration, causing the peroxidation of membrane phospholipids, resulting in loss of cellular compartmentalization (Santos, Menezes, & Villela, 2005;Trawatha, TeKrony, & Hildebrand 1995) and causing a series of chemical reactions, such as hydrolysis and oxidation of lipids, increased acidity (Kong et al, 2008;Thomas et al, 1989) and protein denaturation (Hou & Chang, 2004a;Hou & Chang, 2004b). These events could be responsible for the decrease in solid extraction and especially protein, due to its partial denaturation (Kamizake, Varéa et al, 2014).…”
Section: Physical and Chemical Characteristics Of Soymilk From Aged Gsupporting
confidence: 96%
See 4 more Smart Citations
“…These results are in agreement with those observed by Thomas et al (1989), Chang (2004, 2008) and Kong et al (2008). During storage, the high temperature and relative humidity cause damage to grain tegument and activate the enzymes involved in aerobic respiration, causing the peroxidation of membrane phospholipids, resulting in loss of cellular compartmentalization (Santos, Menezes, & Villela, 2005;Trawatha, TeKrony, & Hildebrand 1995) and causing a series of chemical reactions, such as hydrolysis and oxidation of lipids, increased acidity (Kong et al, 2008;Thomas et al, 1989) and protein denaturation (Hou & Chang, 2004a;Hou & Chang, 2004b). These events could be responsible for the decrease in solid extraction and especially protein, due to its partial denaturation (Kamizake, Varéa et al, 2014).…”
Section: Physical and Chemical Characteristics Of Soymilk From Aged Gsupporting
confidence: 96%
“…This result disagrees with those obtained by Thomas et al (1989), Hou and Chang (1998) and Kong et al (2008). However, Murphy et al (1997) reported a decrease in tofu firmness when it was prepared from aged soybeans, and suggested that this phenomenon could be related to structural changes in protein molecules, particularly the 11S fraction, which is responsible for the firmness of the gel (Tay, Xu, & Perera, 2005).…”
Section: Physical and Chemical Characteristics Of Firm Tofu From Agedcontrasting
confidence: 62%
See 3 more Smart Citations